DIRECTIVE FUNCTIONS IN DRAMA “DEATH OF A SALESMAN” (A Discourse Analysis) - Syahrianti M. Nawir (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2020)
This research aimed at describing the language function especially the directive function used in drama “Death of a Salesman” which focused on act one. This was a descriptive research by using qualitative approach. Method used in this research was library research. The sample of this research was 47 utterances taken from nine scenes (scene 1-9. The writer collected data by using note taking technique. In analyzing data, the writer used descriptive method with following steps : reading the drama, choosing the sentences or utterances which had directive function in it and marked it, classifing the different kinds of directive function, identifying or analyzing the micro function of utterances and concluding the intention or message of drama. The result of this research indicates that there are three kinds of directive function; they are orders, requests, and pleas. Utterances which function as requests then can be subdivided into six groups; they are requests for action, requests for sympathy, requests for information, requests for confirmation, requests for clarification and requests for help. In the chosen utterances there are two utterances (4,3%) which function as order, 35 utterance (74,4%) which function as request and ten utterance (21,3%) which function as plea. The situation of speakers or hearer and the way they utter the utterances can affect the interpretation of utterances.